2016
DOI: 10.1016/j.fertnstert.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and clinical aspects of Mayer-Rokitansky-Küster-Hauser syndrome in a Chinese population: an analysis of 594 patients

Abstract: A lower proportion of associated malformations were found when compared with those provided in the current literature. Renal anomalies were the most frequent associated malformations, and most of the patients presented with a normal karyotype. Given the large cohort of this study, the lower malformation rates might be related to geographic or referral patterns, so further investigation is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 18 publications
3
30
2
2
Order By: Relevance
“…In one of the largest cohort studies of 594 patients with MRKHS, 571 (96.1%) were classified with complete atresia of the vagina (V5b), bilateral aplasia of the cervix (C2b), bilateral aplastic uterus (U4b) and normal adnexa (A0). The most frequent VCUAM classification was V5bC2bU4bA0M0 (M0: no associated malformations), which was diagnosed in 551 (92.8%) of the 594 patients . All the patients with MRKHS showed both complete atresia of the vagina and aplasia of the cervix, as also reported in another large cohort study of 284 patients with MRKHS .…”
Section: Discussionsupporting
confidence: 74%
“…In one of the largest cohort studies of 594 patients with MRKHS, 571 (96.1%) were classified with complete atresia of the vagina (V5b), bilateral aplasia of the cervix (C2b), bilateral aplastic uterus (U4b) and normal adnexa (A0). The most frequent VCUAM classification was V5bC2bU4bA0M0 (M0: no associated malformations), which was diagnosed in 551 (92.8%) of the 594 patients . All the patients with MRKHS showed both complete atresia of the vagina and aplasia of the cervix, as also reported in another large cohort study of 284 patients with MRKHS .…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, Deng et al reported a lower prevalence of renal malformations of only 13% in their Chinese cohort suggesting the possibility of inter-ethnic phenotypical variations in MRKH syndrome from European patient cohorts [15]. Pan et al reported an even lower prevalence of 5% in their Chinese cohort but that study did not include information on the extent of renal examinations performed, which could imply an underestimation of the prevalence [106]. Anomalies of the skeleton are the second most frequent extragenital manifestations in MRKH syndrome affecting around~10-40% depending on the extent of examinations performed and anomalies included (Table 3).…”
Section: Clinical Presentation Diagnosis and Associated Malformationsmentioning
confidence: 96%
“…Also in the cohort of 168 MRKH patients described by Herlin et al, kidney malformations were the most prevalent associated malformations (34.2%). Differently, another recent paper described a cohort of 594 Chinese patients and identified associated malformations in only 7.2% of cases, but renal anomalies were confirmed as the most frequently observed . The different ethnicities of the cohorts may account for the discrepancies among these studies.…”
Section: Mrkh Phenotypesmentioning
confidence: 92%